Letter: Intestinal microbiota transfer – Updating the nomenclature to increase acceptability - Craven,LJ; McIlroy,JR; Mullish,BH; Marchesi,JR (Alimentary Pharmacology and Therapeutics, 2020)
This article is linked to Lai et al paper. To view this article, visit https://doi.org/10.1111/apt.15116